The Emperor Teophilos (829–842) between classicism and exoticism - Pedone, Silvia (Actual Problems of Theory and History of Art, 2015)
The topic which the present paper discusses concerns the art historical (and historiographic) problem of the transmission and reception of ancient models and spoliae during the reign of Theophilos, in a particularly difficult moment, between the Iconoclastic age and the Macedonian one. In the millenary history of Byzantium, the Macedonian period has been seen as the most favourable to a rebirth of Classical antiquity, as it was shown and ideologically attested by artistic display. However, the preceding phase of the affirmation of the Macedonian dynasty has been rather underestimated, and specially the very attitudes of the emperor Theophilos toward art, which are somewhat more complex from an art-historical point of view. Indeed, in the Byzantine art of the period, at least in Constantinople, it is possible to discern a transition from an experimentation and appropriation of exotic features, as some stylistic elements of Islamic art, to a programmatic rebirth of a kind of “classicism” aiming at strengthening the continuity of political power. Thus, besides a taste for experimentation, we find nonetheless an opposite polarity, so far not sufficiently explored, open to a more instrumental or ideological visual strategy, through the re-semantization of Classical art forms because of their “authoritative” association with imperial dignity. In such a perspective, an interesting case is that of the Roman door of Hagia Sophia in Constantinople, the so-called “Beautiful Door”, on which Theophilos placed his own monograms to ratify the endurance of both political and religious authority, on a highly symbolic threshold for Byzantine imagery of power.
Keywords: emperor Theophilos; Byzantine Empire; bronze door; St. Sophia Constantinople; classicism; exoticism; south-west vestibule; Byzantine art